Impact of the use of electronic money on university students (Research, Society and Development, 2017)
The present work is based on the application of descriptive statistics to study the impact of electronic money on Ecuador by students. The objective of the research is to know the students' about the perception of the use of electronic money as a means of payment. The methodology used was based on bibliographical revisions to have the necessary bases on the electronic money, in the same way a quantitative approach was applied, through the personal questionnaire. Subsequently the data processing was carried out with the SPSS software, to perform a descriptive analysis. Among the obtained results it is highlighted that 65.4% of the sample considers the use of electronic money feasible, another of the results found is that there is an ignorance of the advantages and disadvantages of its use, since 39.8% of The sample had knowledge of the subject. Finally you have that university students know or have heard about electronic money. But there is a certain failure because they do not know the advantages and disadvantages of it.